ENT 530 Social Media Portfolio : Kerepek Wonderful / Muhammad Idham Ramli - Ramli, Muhammad Idham (2019)
In this semester, I am taking an entrepreneur subject which is the Principle of Entrepreneurship (ENT530). This subject is one of the requirement for my course by Universiti Teknologi Mara (UiTM). I had been required to do online business and prepared the final report at the end of the semester. In this report I will brief about the business that I have been doing since early of this semester. I already registered my company with Suruhanjaya Syarikat Malaysia. I do have the license to open my own business. The business that I am going to do is to sell snacks. I have become an agent for a snack company and decide to us its product as my product for the assignment. I already get the permission to do this by the owner of the company.